An Anthropological Study of Mummifi ed Remains from the Zeleny Yar Cemetery on the Lower Ob, Western Siberia - A. N. Bagashev; D. I. Razhev; O. E. Poshekhonova; S. M. Slepchenko; E. A. Alekseeva; А. Н. Багашев; Д. И. Ражев; О. Е. Пошехонова; С. М. Слепченко; Е. А. Алексеева (Archaeology, Ethnology & Anthropology of Eurasia, 2017)
Zeleny Yar is a cemetery situated 40 km east of Salekhard, Yamalo-Nenets District. Human remains of 43 individuals from 37 graves have been published so far. Mummifi ed remains were discovered in eight graves dating to the 12th and 13th centuries. We outline the results of a computed-tomography analysis of the best-preserved mummy––that of a male from grave 27. On the basis of examination of endocranial sutures, the individual’s age was estimated at 45–55. Dental pathology includes caries with consecutive apical periodontitis, and osteoarthritis of the left temporomandibular joint. Also, the examination revealed injuries and degenerative-dystrophic postcranial lesions. To analyze the individual’s physical type and reconstruct his face, a plastic cast of the cranium was modeled using the 3D-modeling technique. The male had a Mongoloid appearance. Specifi cally, he can be attributed to the Yamal-Yenisei local variant of the West Siberian race. The modern representatives of this type are the Nenets of the Siberian tundra.